FORMING THE ASSESSMENT MECHANISM OF ENTERPRISES’ INNOVATIVE PROJECTS COMPETITIVENESS - Ekaterina D. Kuzina (Статистика и экономика)
The author proposes a mechanism to estimate the competitiveness of enterprises’ innovative projects. The focus is on the criteria affected the competitiveness of innovative projects. The mechanism of calculating the relative market attractiveness and the relative innovative potential of enterprise to implement innovative project is shown.